Comparative efficacy of orally and topically administered beta blockers for chronic simple glaucoma. Issue 1 (January 1985) - Williamson, J; Young, J D; Atta, H; Muir, G; Kadom, H
Abstract : This open study of beta blockers in chronic simple glaucoma compared the efficacy of once daily (o.d.) oral nadolol therapy with twice daily (b.d.) topical timolol therapy. Sixty eight patients were randomly assigned to starting doses of either 20, 40, or 80 mg of nadolol o.d. (51 patients) or 0.25% timolol b.d. (17 patients) and were seen at weekly intervals for a four-week (short-term) period. Upward dosage titration (80 mg o.d. maximum, nadolol and 0.5% b.d. maximum, timolol) was permitted if, at any visit, the intraocular pressure (IOP) in either eye was greater than 21 mmHg. At the end of 4 weeks the IOPs of a comparable number of patients were controlled (IOP less than 22 mmHg) with 20 mg nadolol o.d. and 0.25% timolol b.d. The 40 mg and 80 mg o.d. nadolol regimens were comparable with each other, superior to the 20 mg regimen, and (at least) equivalent to 0.5% timolol. The absolute degree of IOP reduction achieved with oral nadolol was equivalent to that with topical timolol. Alterations in blood pressure and heart rate were predictably greater with the orally administered beta blocker. Long-term therapy (up to 24 months) in 28 nadolol patients and 5 timolol patients indicates no more likelihood of tolerance with nadolol therapy. Patient withdrawals from the study due to adverse reactions occurred with nadolol but not timolol. Since oral nadolol administered once daily is as efficacious as b.d. topical timolol, it can be recommended as first-line therapy for certain subsets of the glaucoma clinic population.